Spike substitutions E484D, P812R and Q954H mediate ACE2-independent entry of SARS-CoV-2 across different cell lines - Greta Vizgirda; Alexander P. Underwood; Ulrik Fahnøe; Nina Weis; Santseharay Ramirez; Jens Bukh (PLoS ONE, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), has evolved into variants with multiple spike protein coding mutations that affect its transmissibility, infectivity, and immune evasion, in particular from neutralizing antibodies. Several of these amino acid changes have been associated with reduced dependency on the principal angiotensin converting enzyme-2 (ACE2) receptor for cell entry. The present study investigates the role of spike protein changes observed in a cell-culture adapted SARS-CoV-2 isolate (DK-AHH1) in modulating entry, ACE2 dependency, and neutralization across different cells, including human liver and lung cell lines. Using a pseudoparticle system, spike proteins with substitutions E484D, P812R, Q954H, and deletion Δ68−76 were evaluated in Vero E6 and Huh7.5, as well as in A549 cells with and without ACE2 overexpression. Pseudoparticles carrying E484D or P812R individually permitted entry in Huh7.5 cells, and their combination further enhanced this capacity. ACE2 blocking experiments revealed the differential roles of these mutations in mediating entry across cell lines. In Vero E6 cells, P812R was the primary driver for ACE2-independent entry, while E484D facilitated ACE2-independent entry in Huh7.5 cells. In A549 cells, all three substitutions (E484D+P812R + Q954H) were required for ACE2-independent entry. Addition of the Δ68−76 deletion did not increase infectivity in any cell line. Notably, pseudoparticles carrying these mutations, maintained susceptibility to neutralization by convalescent plasma from subjects with COVID-19, regardless of the cell line used. These findings highlight the adaptability of SARS-CoV-2 in utilizing alternative entry mechanisms across various cell types, with E484D and P812R playing critical roles in ACE2-independent entry in cell culture. Overall, this study provides valuable insights into how SARS-CoV-2 can alter its receptor usage to ensure robust infectivity of human cell lines while preserving neutralization sensitivity, contributing to our understanding of viral evolution, and informing potential therapeutic strategies targeting viral entry.